The study of antimicrobial properties of immobilized fibrous N-chloro sulfonamides - V. N. Toropіn; Е. V. Surmasheva; L. I. Romanenko (Zaporozhye State Medical University, 2016)
Aim. The determination of antibacterial and antifungal action of nonwoven form of N-chloro sulfonamides immobilized on a polypropylene fiber with a graft copolymer of styrene and divinylbenzene. Materials and methods. The object of the study was a non-woven form of sodium N-chloro sulfonamides immobilized on a polypropylene fiber with a graft copolymer of styrene and divinylbenzene. Determination of antibacterial and antifungal action of the material was carried out by the "agar plate" at the meat peptone agar (МPA). As the test cultures of microorganisms we used: E.coli, S.aureus and C.albicans. Microbial load was 1х107 TEM/ml. Results. The growing delay for such test microorganisms as E. coli strains, S.aureus and C.albicans fungi has been observed only for samples of material. Lack of microbial growth delay zones outside the samples occurs due to poor contact with the surface of the MPA. The method of "agar plate" has been changed to obtain reliable results of antibacterial and antifungal action of the material. The test material samples were placed in uncured MPA, the further experiment was carried out according to standard procedures of the "agar plates" method. Latency test microorganism growth around the sample material lies in the range 6,0 -7,0 mm - for E.coli; 16,0 -25,0 mm - for S.aureus; 4,0 -6,0 mm - for C.albicans. These results are explained by activation with the help of ammonium salts and amino acids, which release the active material of chlorine in case when the material contacts with the liquid nutrient medium. Evidently, this way the material will behave in contact with the skin of human (or animal). In contact with the dry skin covering the material will remain inactive, but in contact with the wound the release of active chlorine will occur within a specified period of time, whereby the material can protect the wound from infection. Conclusions. Antibacterial and antifungal properties of non-woven form of sodium N-chloro sulfonamides immobilized on a polypropylene fiber with a graft copolymer of styrene and divinylbenzene are determined by the degree of contact with ammonium salt solutions and amino acid nutrient medium. While the surface contacts the growth inhibition of test cultures of microorganisms occurs only under the material. Introducing the material into a liquid medium greatly increases its activity. Thus, the material exhibits pronounced antimicrobial properties against the above test strains of microorganisms.